Python parallel programming cookbook: master efficient parallel programming to build powerful applications using Python - Zaccone, Giancarlo (Quick Answers to Common Problems, 2015)
About This BookDesign and implement efficient parallel softwareMaster new programming techniques to address and solve complex programming problemsExplore the world of parallel programming with this book, which is a go-to resource for different kinds of parallel computing tasks in Python, using examples and topics covered in great depthWho This Book Is ForThis book is intended for software developers who want to use parallel programming techniques to write powerful and efficient code. After reading this book, you will be able to master the basics and the advanced features of parallel computing. The Python programming language is easy to use and allows nonexperts to deal with and easily understand the topics exposed in this book.